Study on the effect of soil moisture content and plowing speed on draft requirements of a moldboard plow (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
This study was conducted to study the effect of soil moisture content and plowingspeed of the implement on draft force of a moldboard plow (mounted-type). Three soil moisture content (5.08, 5.14 and 6.82 %db) and three plowing speed (2.67, 3.95 and 4.53 km/h) were investigated. The average tillage depth was 20 cm and the average soil bulk density was 1.73 g/cm3.The experiment was laid out in a randomized complete block design with two replications. The data collected were subjected to analysis of variance (ANOVA). Also, Least Significant Difference Test (LSD) at 5% probability was performed to compare the means of different treatments. The statistical results of the study indicated that soil moisture content and plowing speed significantly (P < 0.05) affected draft force. Draft force also decreased by increasing soil moisture content and increased by increasing plowing speed.